Effect of text messages online education for premenstrual syndrome symptoms using media-based support in Iranian Students - Parisa Davarei; Ali Khani Jeihooni; Arash Ziapour; Fakhreddin Chaboksavar; Mahboobeh Nasiri; Azadeh Ghanbarnia; Aysa Azami; Abolfazl Atashpoosh; Fatemeh Mohammadkhah (Shahrekord University of Medical Sciences, 2023)
Background and aims: One of the most common complaints of women is premenstrual syndrome (PMS). This study aimed to determine the effect of text messages online Education on PMS using Media-based Support. Methods: The present research was an interventional quasi-experimental study from May 2021 to August 2021 in all female students in Ramsar city, Iran. Sixty-eight cases were selected and divided into two groups (the intervention and control groups). Demographic characteristics questionnaire and Premenstrual Symptoms Questionnaire (PSQ) were used. Each case in the experimental group received text messages for three menstrual cycles. PMS symptoms were compared before and after the intervention in two groups. The data were analyzed using SPSS software (version 16), independent t-test, paired t-test, and covariance analysis (P=0.005). Results: The participants were 18-25 years old and were studying for a bachelor's degree. Before the intervention, the mean of the PMS score was (11.25±10.05) in the Intervention group and (31.38±14.31) in the Control group (P=0.041). After the intervention, the mean PMS scores in the Intervention and Control groups were (21.85±8.25) and (33.26±14.45) (P=0.001). In the intervention group, psychological and physical symptoms were statistically significant before (25.11±10.05) and after the intervention (21.85±8.25) (P=0.007). Conclusion: The study results showed that media-based support is an efficient and effective method in reducing premenstrual symptoms, which can be used in related interventions as an effective, easy, and low-cost method.